MALNUTRISINAN Malnutrition solusyonan sa asinan. - Bacallan, Jed Vincent; Caro, Miguel Angelo; Reyes, Fate Delos (2014.)
A cross sectional study was conducted in Janiuay, Iloilo involving tricycle drivers and jeepney drivers. The objective of the study was to determine and compare the prevalence and risk factors of hypertension and obesity between public utility jeepney and tricycle drivers in Januiay, Iloilo. A total of 165 respondents, jeepney (87) and tricycle (78), were measured with an aneroid sphygmomanometer and tape measure to determine the blood prressure and waist-hip ratio. An interview was also conducted to determine occupational factors and lifestyle habits. Results were analyzed through SPSS using Chi-square test, T-test and Odss ratio. The prevalence of hypertension was found to be greater in jeepney drivers (36.80 percent) compared to tricycle drivers (34.60 percent). The prevalence of obesity was found to be greater in tricycle drivers (46 percent) compared to jeepney drivers (45 percent). There is a significant difference in the occupatonal risk factors between jeepney drivers and tricycle drivers, years of driving, average trip time, kilometers travelled per day and number of trips per day (p<0.0005). However, working days per week (p<0.08) and working hours per day (p<0.30) showed no significant difference between two populations. The results of the odds ratio showed no significant effect in all lifestyle factors to hypertension and obesity. There is no significant difference in the prevalence of hypertension, obesity and lifestyle risk factors between jeepney drivers and tricycle drivers. However there is a significant difference in the occupational risk factors between the two driver populations.
Community Project (Undergraduate, Bachelor of Science in Public Health) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Malnutrition -- Janiuay, Iloilo